La interpretación de Heidegger de Heráclito : physis, logos y harmonia (2017)
"This research intends to rescue the ontological thought of Heraclitus of Ephesus under the light of the interpretations of Martin Heidegger, along with some own contributions from special categories present in its fragments and testimonies. It is intended to unravel the metaphysical content suggesting a renewed reading of the problem of assembly, the internal connection of nature, the human representation of being and the opening of being, and the correlation of opposites in other terms than simple opposition. We seek to endow Heraclitus' thesis on nature with stronger ontological ground and to consolidate a model metaphysical form to think of being as a constant becoming" -- Tomado del Formato de Documento de Grado.